PROFILE OF DROWNING DEATHS AMONG MEDICOLEGAL AUTOPSIES CONDUCTED AT KADAPA, ANDHRA PRADESH: A 2-YEAR RETROSPECTIVE STUDY - B, Venkatesulu; S, Sudhakar; M, Abdul Khalid; G, DINESH; NAIK M, SRINIVASA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Drowning kills at least 372,000 people every year and is the 3rd leading cause of unintentional deaths. In addition to the human tragedy, drowning represents a huge economic problem with direct and indirect costs, including many Disability-Adjusted Life Years lost. In India, very little is known about the epidemiology of drowning. The objective of the study was to study the incidence, manner, and epidemiology of deaths due to drowning in and around Kadapa region. Methods: The present study was conducted from January 2021 to December 2022 in Government Medical College, Kadapa on 154 cases to study the various epidemiological parameters of drowning. Results: In the study period, 1246 cases of postmortem examination were done, of which 154 cases were of drowning related deaths. A maximum number of cases were seen in the age group of 21–30 years with males 70.77% dominating the study population. 50.64% of deaths were accidental in nature and occurred during the rainy season. The most common place of occurrence of drowning was river 57.14% followed by wells 14.28%. Soddening of hands and feet was the most common external feature of drowning followed by the presence of froth at mouth and nostril. Conclusion: Drowning is a most ignored public hazard worldwide with serious implications for the society. Public awareness regarding safety measures and drowning prevention strategies suitable to the needs of geographical region should be adapted.